Analisa Dan Perancangan Jaringan Dengan Verry-Small Aperture Terminal (VSAT) Pada PT. Pertamina Offshore North West Java (PHE ONWJ) - Subarno (CV. Multi Kreasi Media, 2024)
A satellite is simply defined as any moving object around another object (which is usually much larger) in a path which can be estimated mathematically called an orbit satellite) Satellite is an alternative communication technology that can be applied to meet communication needs in areas with archipelagic geographical conditions. One of the existing satellite communication systems is VSAT IP. VSAT IP applies TDM/TDMA technology with IP as the communication protocol. A hub station that is central in a telecommunications network with a star topology is connected to several remote stations using shared satellite bandwidth for several remote stations. Some of the parameters used to determine the reliability of VSAT IP include delay, data rate and service level. The reliability of PT Pertamina's VSAT IP communication system reaches an SLA of 99.95%. This value is the result of the calculation of the service level, and the result has exceeded the standard set by PT Pertamina, which is 99.5%. However, VSAT IP communication has a high delay. Transmission delay and latency are 250 milliseconds for one link (up and down link). The capacity on one satellite can reach 150 Gbps. The long process of sending data packets causes the processing time and data transmission between devices to also get longer. With such a delay value and data rate, VSAT IP can still serve data communication well, that's because in VSAT IP there are TCP spoofing and ACK Reduction features. A reliable network system will be able to serve all data traffic both in various situations of low and high traffic.